2020
DOI: 10.1002/jso.25963
|View full text |Cite
|
Sign up to set email alerts
|

Predictors of lymph node metastases in patients with mucinous appendiceal adenocarcinoma

Abstract: Background Lymph node metastasis (LN+) is a prognostic factor in appendiceal cancers, but predictors and outcomes for LN+  in mucinous appendiceal adenocarcinoma (MAC) remain poorly defined. Methods Patients were identified from the 2010 to 2016 NCDB who underwent surgical resection as first‐line management for Stage I‐III mucinous appendiceal cancer. A LN+ risk‐score model was developed using multivariable regression on a training data set and internally validated using a testing data set. Three‐year overall … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 22 publications
0
7
0
Order By: Relevance
“…This study showed that lymph node metastasis was an independent prognostic biomarker associated with lower cancer-specific survival in all histological types except MiNENS and NETs and overall survival in all histological types except NETs. Lymph node metastasis has not been associated with lower survival in patients with MAC [ 28 ]. Interestingly, this study found that cleaning > 12 lymph nodes was associated with improved cancer-specific survival and overall survival in all patients combined, or in NMAC, MAC, SRCC and GCC, but only with improved overall survival in patients with MiNENs.…”
Section: Discussionmentioning
confidence: 99%
“…This study showed that lymph node metastasis was an independent prognostic biomarker associated with lower cancer-specific survival in all histological types except MiNENS and NETs and overall survival in all histological types except NETs. Lymph node metastasis has not been associated with lower survival in patients with MAC [ 28 ]. Interestingly, this study found that cleaning > 12 lymph nodes was associated with improved cancer-specific survival and overall survival in all patients combined, or in NMAC, MAC, SRCC and GCC, but only with improved overall survival in patients with MiNENs.…”
Section: Discussionmentioning
confidence: 99%
“…As supported by previous evidence, the risk of lymph node metastasis in AA correlates with the grade of differentiation, depth of tumoral invasion (T stage), presence of lymphovascular invasion, histologic subtype, and margin status. [4][5][6][13][14][15][16] Because of their unique biological behavior, mucinous AAs have a higher risk of serosal invasion and peritoneal seeding than lymph node metastasis compared with nonmucinous, colonic-type AAs. This risk significantly increases with moderately and poorly differentiated disease.…”
Section: Discussionmentioning
confidence: 99%
“…This risk significantly increases with moderately and poorly differentiated disease. 15,16 In a study from the Surveillance, Epidemiology, and End Results database, Xie et al 17 analyzed 1404 patients with stage I to IV AA from 2004 to 2013 to determine the association between various clinicopathologic variables and OS. The authors found that extended resection (RH, total colectomy) offers a 5-year OS benefit for patients with tumoral invasion beyond the mucosal layer (≥T2), whereas for T1 disease, no difference in the 5-year OS was found between patients who underwent local resection compared with patients who underwent more extensive resections.…”
Section: Discussionmentioning
confidence: 99%
“…It remains unclear whether patients with unruptured mucinous adenocarcinoma of the appendix should undergo right hemicolectomy. Many centres opt for observation in lower grade cancers 9 . The literature on appendiceal stump adenocarcinoma is limited and it is unclear whether a more aggressive surgical approach should be taken to management.…”
Section: Figurementioning
confidence: 99%
“…Many centres opt for observation in lower grade cancers. 9 The literature on appendiceal stump adenocarcinoma is limited and it is unclear whether a more aggressive surgical approach should be taken to management. One review found that most cases of remnant appendix cancer required further extensive surgery but this was largely attributed to a delayed diagnosis resulting in complications requiring more extensive surgery.…”
mentioning
confidence: 99%